Clinicopathological Study of Optimal Ranges for Lymph Node Dissection in Cancer of the Transverse Colon - Ihara, Atsushi; Nozawa, Tadashi; Sakakibara, Yuzuru; Hiki, Yoshiki; Aihara, Shigeki; Kokuba, Yukihito; Otani, Yoshimasa; Kakita, Akira (Nippon Shokaki Geka Gakkai zasshi, 1997)
The subjects were 79 (7.5%) patients who had undergone resection of transverse colon cancer among 1060 patients with colorectal cancer which had been resected in our hospital during the 11 years from April 1986, when the hospital was founded, to March 1996. In those 79 patients grades of lymph node metastasis wree distributed as follows: n0, 45 (57.0%); nl, 14 (17.7%); n2, 7 (8.9%); n3, 3 (3.8%); and n4 (SMA+, hereinafter), 10 (12.7%) patients. Of these patients with lymph node metastatis, a clinical problem exists in patients with SMA + (10 cases in the present study) which likely results in insufficient dissection of the lesions by transverse colectomy together with lymph node dissection (D3). Therefore in the present study, we investigated the prognosis for such the SMA+ patients and also risk factors for the cases. The results, regarding optimal ranges for the lymph node dissection in cancer of the transverse colon and other findings, include the following. First, patients with cancer of the transverse colon showing intramural extension of mp or less do not show lymph node metastasis indicating eligibility for resection of the transverse colon. Second, risk factors for lymph node metastasis along the SMA are: 1) intramural extension, ss or more; 2) histological types, poorly differentiated and undifferentiated carcinoma; 3) intravascular invasions ly2/v2 or more; 4) infiltration (INF) modes, INFβ and INFγ; 5) tumor diameter, 3cm or more. And finally, results in the present study suggest that extended right hemicolectomy meaning not clear dissection of the surgical trunk should be performed for patients who show advanced transverse colon cancer with intramural extension of ss or more and with any one of the characteristics described in 2-5) of item 2 above.